Cooling effect of urban river reserve vegetation structure in outdoor environment - Siti Rahmah Omar, 1983-, author; Johan Sohaili, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2019